Christians under covers : evangelicals and sexual pleasure on the Internet - Burke, Kelsy, 1985- (Oakland, California : University of California Press, 2016)
"Christians under Covers shifts how scholars and popular media talk about religious conservatives and sex. In an ethnography drawn from Christian sexuality websites, Kelsy Burke examines how some evangelical Christians use digital media to promote the idea that God wants married, heterosexual couples to have satisfying sex lives. These evangelicals maintain their religious beliefs while incorporating feminist and queer language into their talk of sexuality--encouraging sexual knowledge, emphasizing women's pleasure, and justifying marginal sexual practices within Christian marriages. This book complicates boundaries between normal and subversive, empowered and oppressed, and sacred and profane"--Provided by publisher.
Godly sex : a new evangelical sexual logic -- Overcoming the obscene : using religion to talk about sex -- Virtual and virtuous : forming online religious communities -- Sexual awakening : defining women's pleasures -- What makes a man : making "bad" sex "good" -- Conclusion : paths of desire -- Appendix A : websites mentioned by name in the book -- Appendix B: doing internet ethnography.
Includes bibliographical references and index.
Keywords: Christians -- Sexual behavior -- United States; Sex -- Religious aspects -- Christianity; Internet -- Religious aspects -- Christianity; Sex in mass media; USA